Alcohol Binge Drinking Selectively Stimulates Protein S-Glutathionylation in Aorta and Liver of ApoE−/− Mice - Seidel, Kerstin; Wan, Xueping; Zhang, Mo; Zhou, Yuxiang; Zang, Mengwei; Han, Jingyan (Frontiers in Cardiovascular Medicine, 2021)
Background: Binge drinking has become the most common and deadly pattern of excessive alcohol use in the United States, especially among younger adults. It is closely related to the increased risk of cardiovascular disease. Oxidative stress as a result of ethanol metabolism is the primary pathogenic factor for alcohol-induced end organ injury, but the role of protein S-glutathionylation—a reversible oxidative modification of protein cysteine thiol groups that mediates cellular actions by oxidants—in binge drinking-associated cardiovascular disease has not been explored. The present study defines the effect of alcohol binge drinking on the formation of protein S-glutathionylation in a mouse model of atherosclerosis. Methods and Results: To mimic the weekend binge drinking pattern in humans, ApoE deficient (ApoE−/−) mice on the Lieber-DeCarli liquid diet received ethanol or isocaloric maltose (as a control) gavages (5 g/kg/day, 2 consecutive days/week) for 6 weeks. The primary alcohol-targeted organs (liver, brain), and cardiovascular system (heart, aorta, lung) of these two groups of the mice were determined by measuring the protein S-glutathionylation levels and its regulatory enzymes including [Glutaredoxin1(Grx1), glutathione reductase (GR), glutathione-S-transferase Pi (GST-π)], as well as by assessing aortic endothelial function and liver lipid levels. Our results showed that binge drinking selectively stimulated protein S-glutathionylation in aorta, liver, and brain, which coincided with altered glutathionylation regulatory enzyme expression that is downregulated Grx1 and upregulated GST-π in aorta, massive upregulation of GST-π in liver, and no changes in Grx1 and GST-π in brain. Functionally, binge drinking induced aortic endothelial cell function, as reflected by increased aortic permeability and reduced flow-mediated vasodilation. Conclusions: This study is the first to provide in vivo evidence for differential effects of binge drinking on formation of protein S-glutathionylation and its enzymatic regulation system in major alcohol-target organs and cardiovascular system. The selective induction of protein S-glutathionylation in aorta and liver is associated with aortic endothelial dysfunction and fatty liver, which may be a potential redox mechanism for the increased risk of vascular disease in human binge-drinkers.